OPTIMALISASI SALURAN PENAMBAH PADA CORAN ROLL PRESS - Suratman, Rochim; Yudiyanto, Oyok (Mesin, 2002)
The high yield rate of casting product indicates the efficiency of casting process. Yield of casting is defined as a ratio between the casting weight to the total weight included the riser and gating system. Increasing yield could be accomplished through the optimizing of riser. Trial and error of the existing alternative designs is the most commonly method. This requires a lot of time and money. Computer software is used in order to reduce this effort. The applied software is AFS solidification system which enable us to simulate the cooling and solidification process. The alternative designs could be simulated on the computer. By using FCD 700 as the base material of Roll press, the research gave an increase of yield, i.e. from 68,5 % yield to 76,6%. yield This is significant for a casting weight of 139 kg.